2022
DOI: 10.1088/1741-4326/ac7476
|View full text |Cite
|
Sign up to set email alerts
|

The role of ETG modes in JET–ILW pedestals with varying levels of power and fuelling

Abstract: We present the results of GENE gyrokinetic calculations based on a series of JET-ILW type I ELMy H-mode discharges operating with similar experimental inputs but at different levels of power and gas fuelling. We show that turbulence due to electron-temperature-gradient modes (ETGs) produces a significant amount of heat flux in four JET-ILW discharges, and, when combined with Neoclassical simulations, is able to reproduce the experimental heat flux for the two low gas pulses. The simulations plausibly reproduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“… 7 Chapman-Oplopoiou et al (2022) found such a scaling of the heat flux with in their investigations of nonlinear pedestal turbulence driven by ETG modes [see their equation (1), and the following discussion] suggesting, perhaps, that this scaling may hold in more realistic – and complex – plasma systems than that considered here.…”
mentioning
confidence: 55%
“… 7 Chapman-Oplopoiou et al (2022) found such a scaling of the heat flux with in their investigations of nonlinear pedestal turbulence driven by ETG modes [see their equation (1), and the following discussion] suggesting, perhaps, that this scaling may hold in more realistic – and complex – plasma systems than that considered here.…”
mentioning
confidence: 55%
“…For example, Chapman-Oplopoiou et al. (2022) performed nonlinear, electromagnetic simulations of JET–ILW pedestals for , and observed the same scaling of the heat flux with as (2.7) at gradients sufficiently far above the linear threshold. However, if the outer scale lies on scales larger than the flux-freezing scale, i.e.…”
Section: Summary and Discussionmentioning
confidence: 86%
“…2022, Chapman-Oplopoiou et al. 2022 and Field et al. 2023, where a strong dependence of the heat flux on the equilibrium density gradient was identified).…”
Section: Collisional Fluid Modelmentioning
confidence: 96%
“…In H-mode [1,2] tokamak plasma, electron fluxes can be driven by a rich variety of waves and instabilities covering a large range of temporal and spatial scales making its modeling (in terms of its width and height) challenging. Effectively, several studies on the origin of the electron heat transport in the pedestal region [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21] show that drift-wave, such as the electron-temperature-gradient (ETG) instability, the trapped-electron mode (TEM), and electromagnetic instabilities, such as kinetic-ballooning mode (KBM) and microtearing (MT) modes of interest here, can explain the electron heat transport observed experimentally. These instabilities can develop in the pedestal region, leading to turbulence, which affects the transport and the confinement of heat and particles.…”
Section: Introductionmentioning
confidence: 94%